2007
DOI: 10.1007/s10681-007-9406-6
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine-induced chromosome doubling in Platanus acerifolia and its effect on plant morphology

Abstract: We report the production of tetraploid plants of Platanus acerifolia, with the ultimate aim of improving the ornamental qualities of this important urban landscaping tree. Chromosome doubling was achieved by the application of colchicine to either pre-soaked seed or to the apical meristems of young seedlings. Treatment of the ungerminated seed was the more eYcient method in terms of numbers of tetraploid seedlings (up to 40%, as determined by chromosome counting of the root-tip nuclei) but this method produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
81
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 29 publications
20
81
0
5
Order By: Relevance
“…Nakasone (1960) reported that treatment of Vanda and Dendrobium seeds with colchicine of 1000 up to 10000 mg L -1 for more than four days caused interference on their germination. Similar results were also reported in non-orchid plants, in Cyclamen seeds by Takamura and Miyajima (1996) and Platanus acerifolia seeds by Liu et al, (2007). …”
Section: Fruit (Pod) Forming and In Vitro Seed Germinationsupporting
confidence: 88%
“…Nakasone (1960) reported that treatment of Vanda and Dendrobium seeds with colchicine of 1000 up to 10000 mg L -1 for more than four days caused interference on their germination. Similar results were also reported in non-orchid plants, in Cyclamen seeds by Takamura and Miyajima (1996) and Platanus acerifolia seeds by Liu et al, (2007). …”
Section: Fruit (Pod) Forming and In Vitro Seed Germinationsupporting
confidence: 88%
“…Eeckhaut (2003) also only regenerated chromosome doubled plants when B. davidii seeds were treated with oryzalin and trifluralin. This concurs with results in other genera, such as Platanus, where treatment of (ungerminated) diploid seeds with colchicine was the most efficient method to obtain tetraploid seedlings (Liu et al 2007). The use of nodal sections has some advantages over the treatment of seed(lings); only one selected genotype is treated when using nodal sec- tions.…”
Section: In Vitro Polyploidisation Of B Globosasupporting
confidence: 89%
“…For Acacia crassicarpa (Fabaceae), the effective concentration was 0.001-0.020% (Harbard et al 2012). For plants in the genera of Paulownia (Scrophulariaceae) and Platanus (Platanaceae), it was 0.05% and 0.4%, respectively (Liu et al 2007;Tang et al 2010). The score of treatment conditions for E. ulmoides was within the range of these woody plants; its sensitivity to colchicine might lie about halfway within the scores of treatment conditions reported for other woody plants.…”
mentioning
confidence: 73%